KARAKTERISASI DAN PENAPISAN FITOKIMIA SIMPLISIA WORTEL SERTA REVIEW KANDUNGAN KIMIA DAN AKTIVITAS FARMAKOLOGI WORTEL (DAUCUS CAROTA L.) - Rika Hartati; Fidrianny, Irda; Fitria, Alfiyani (Acta Pharmaceutica Indonesia, 2024)
Carrot is an important source of nutrition for humans and a good source of dietary fiber. Carrot are rich in bioactive compounds such as phenolic compounds, carotenoids, polyacetylene, and ascorbic acid which has health effects. Carrot are known to have many health benefits such as antioxidants, antidiabetic, antiinflammatory, antihypertensive, antibacterial, and antifungal. This study aims to determine the characteristics and phytochemical screening of root, leaves and stem carrot (Daucus carota L) and prepare a review article about chemical compounds and pharmacological activities of carrot. Characterization performed of crude drug included macroscopic and microscopic, determination of total ash content, acid insoluble ash, water soluble ash, water content, water soluble extract, ethanol soluble extract, and loss on drying. Phytochemical screening was carried out to check the presence of secondary metabolite in crude drug. Root, leaves and stem of carrot extracted by reflux method with n-hexane, ethyl acetate, and 96% ethanol. Review article was prepared by considering and analyzing literatures. Water content of roots, leaves and stem of carrot were 5%, 4,17% and 6,67%, respectively. All crude drugs contained flavonoid, phenol, quinone and steroid/triterpenoid groups. Article review was done by collecting and analysing 82 literatures. The water of all crude drugs fulfilled the requirement. Wortel (Daucus carota L.) has many chemical compounds and pharmacological activities. Keywords: carrot, characterization, phytochemical screening, chemical compounds, pharmacological activities